2008
DOI: 10.1242/jcs.035063
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin-I- and synapsin-II-null mice display an increased age-dependent cognitive impairment

Abstract: mice during aging. Both SynI-/-and SynII -/-mice displayed behavioural defects that emerged during aging and involved emotional memory in both mutants, and spatial memory in SynII -/-mice. These abnormalities, which were more pronounced in SynII -/-mice, were associated with neuronal loss and gliosis in the cerebral cortex and hippocampus. The data indicate that SynI and SynII have specific and non-redundant functions, and that synaptic dysfunctions associated with synapsin mutations negatively modulate cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 74 publications
9
68
1
1
Order By: Relevance
“…Our results are consistent with existing reports showing that reduction in synapsin-I gene expression induced by increased DNA methylation is linked to cognitive aging in rodents (43) and that ablation of either the synapsin-I or synapsin-II gene causes age-dependent cognitive impairment in mice involving emotional and spatial memory (44). Of note, 12-to 14-mo-old SYN1-null mice display neuronal loss and gliosis in the hippocampus and neocortex (44) further highlighting the importance of putative changes in synapsin expression in AD. In addition, SYN1 and SYN2 loss-of function mutations in humans were recently shown to be causative for autism spectrum disorder (45,46), associated with excitatory/inhibitory imbalance and epileptic seizures (47).…”
Section: Synapsin-i/ii Lowering and Cognitive Deficits In Ad And Animalsupporting
confidence: 93%
“…Our results are consistent with existing reports showing that reduction in synapsin-I gene expression induced by increased DNA methylation is linked to cognitive aging in rodents (43) and that ablation of either the synapsin-I or synapsin-II gene causes age-dependent cognitive impairment in mice involving emotional and spatial memory (44). Of note, 12-to 14-mo-old SYN1-null mice display neuronal loss and gliosis in the hippocampus and neocortex (44) further highlighting the importance of putative changes in synapsin expression in AD. In addition, SYN1 and SYN2 loss-of function mutations in humans were recently shown to be causative for autism spectrum disorder (45,46), associated with excitatory/inhibitory imbalance and epileptic seizures (47).…”
Section: Synapsin-i/ii Lowering and Cognitive Deficits In Ad And Animalsupporting
confidence: 93%
“…Interestingly, it has been shown that aged synapsin I-deficient mice display an increased loss of neurons in the neocortex and hippocampus (Corradi et al, 2008) and that stress-related memory induced by a glucocorticoid-triggered signaling pathway is synapsin dependent (Revest et al, 2010), indicating an important function of synapsin for neuronal survival following exposure to stress.…”
Section: Extracellular Synapsin Stimulates Neurite Outgrowth and Is Nmentioning
confidence: 99%
“…For example, in synapsin I-and II-null mice, synapses are still formed but are not fully functional because the RPSV is dramatically decreased. The mice demonstrate defects in synaptic plasticity (more pronounced synaptic depression), age-related cognitive decline, and epileptic seizures (14). Mutations in synapsin I have also been found in patients with epilepsy and autism spectrum disorders (15,16).…”
Section: O-glcnac and Enzymes Executing Its Turnover (O-glcnac Transfmentioning
confidence: 99%